Human trafficking in Brazil: the State against migrants (Ágora Journal, 2022)
This article aims to analyze how Brazil has developed legislation and migration policies, historically, recently and in the context of the pandemic, considering the importance of combating human trafficking. In Brazil, its confrontation emerged relatively recently as a national public policy, despite being a phenomenon that has been present since the beginning of colonization. Through a bibliographic and documentary study and based on the authors' professional experience, it is shown that, even recognizing the importance, in practice the Brazilian State has complicated the fight against it and even aggravate the situation of trafficking persons, through its selective and repressive migration policies and labor policies both limited and increasingly dismantled. This has restricted the rights of migrants, maintaining and expanding space for slave labor, the main destination for human trafficking. This contradiction of the Brazilian State calls for an urgent review and repositioning of strategies to guarantee the rights of people in situations of vulnerability or victimized by human trafficking.
Keywords: Human Trafficking; Migration; Nation/State